2016
DOI: 10.1007/s11010-016-2754-6
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the brain antioxidant status: modulation by dietary supplementation of Decalepis hamiltonii and physical exercise

Abstract: The synergistic effects of physical exercise and diet have profound benefits on brain function. The present study was aimed to determine the effects of exercise and Decalepis hamiltonii (Dh) on age-related responses on the antioxidant status in discrete regions of rat brain. Male Wistar albino rats of 4 and 18 months old were orally supplemented with Dh extract and swim trained at 3 % intensity for 30 min/day, 5 days/ week, for a period of 30 days. Supplementation of 100 mg Dh aqueous extract/kg body weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 45 publications
(48 reference statements)
1
15
0
Order By: Relevance
“…[4] Recent studies from our laboratory have demonstrated that dietary supplementation of Dh extract along with swim exercise helps in attenuating the OS in the aging rat brain. [5] Our studies also demonstrated that 4-HIA and EA are the major phenolic acids which exhibit potent antioxidant activities and inhibits lipid peroxidation (LPO) against AAPH induced OS in rat brain in vitro . [6] Therefore, the present study was hypothesized to investigate the effects of dietary supplementation of Dh extract, EA, and 4-HIA in curtailing the OS in the aging rat brain.…”
Section: Introductionmentioning
confidence: 77%
“…[4] Recent studies from our laboratory have demonstrated that dietary supplementation of Dh extract along with swim exercise helps in attenuating the OS in the aging rat brain. [5] Our studies also demonstrated that 4-HIA and EA are the major phenolic acids which exhibit potent antioxidant activities and inhibits lipid peroxidation (LPO) against AAPH induced OS in rat brain in vitro . [6] Therefore, the present study was hypothesized to investigate the effects of dietary supplementation of Dh extract, EA, and 4-HIA in curtailing the OS in the aging rat brain.…”
Section: Introductionmentioning
confidence: 77%
“…Oxidative stress in brain is related with many factors such as environmental toxin, aging, and diseases. Previous studies have shown oxidative stress could be alleviated by environmental enrichment ( 17 , 24 , 53 ), and the dramatic effect can be shown in the aging rat brain ( 17 , 24 ). EE also mediates various functional improvements via the increased expression of growth factors such as FGF-2 in the hypoxic ischemic mice ( 14 ).…”
Section: Discussionmentioning
confidence: 98%
“…Environmental enrichment (EE) is a rehabilitation strategy for rodents and the enhancement of the brain by surroundings that include various objects such as running wheels, novel toys and allow large social interactions to experience the effects of a complex combination of physical, cognitive, and social stimulation in the brain ( 14 16 ). In many studies, EE has been implicated in improvement of the brain functions such as neuroprotection and neurogenesis in an animal model of aging ( 17 20 ), ischemic brain injury ( 14 ), and neurodegenerative diseases ( 14 , 21 ). These diseases and brain injuries, accompanied with an increase in oxidative stress and olfactory impairment, eventually lead to a clinically significant problem ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional improvements in neurological diseases have been proven by EE in several studies [ 17 ]. Moreover, various neurochemical and histological hypotheses have been suggested for the underlying mechanisms of this improvement, including reduced oxidative stress, anti-neuroinflammation, neurogenesis, synaptic plasticity, and neuroprotection via the induction of neurotrophic factors [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%